Emotional Responses (verbal and psychophysiological) to pictures of food stimuli - Esteves, Francisco (2010)
Emotional processing of food-related pictures was studied in four experiments, comparing participants who revealed unhealthy attitudes toward food, dieting and body shape with control groups. All subjects were female and responses to pictures of low and of high calorie foods were compared to responses to other emotional stimuli. The first three experiments measured verbal and autonomic responses and Experiment 4 was a classical conditioning study. In Experiments 2-4, pictures were presented backward masked in order to observe automatic, non-conscious responses. The results showed that, in general, food pictures were processed in the same way as other emotional material, both verbally and psychophysiologically. Although there were some results indicating a difference between groups, the general pattern was that participants selected for being more worried about food and dieting did not show higher reactivity to food cues.